Photochemical vs. Bacterial Control of H2O2 Concentration Across a pCO2 Gradient Mesocosm Experiment in the Subtropical North Atlantic - Hopwood, Mark J.; Riebesell, Ulf; Arístegui, Javier; Ludwig, Andrea; Achterberg, Eric P.; Hernández, Nauzet (Frontiers in Marine Science, 2018)
In the surface ocean, microorganisms are both a source of extracellular H2O2 and, via the production of H2O2 destroying enzymes, also one of the main H2O2 sinks. Within microbial communities, H2O2 sources and sinks may be unevenly distributed and thus microbial community structure could influence ambient extracellular H2O2 concentrations. Yet the biogeochemical cycling of H2O2 and other reactive oxygen species is rarely investigated at the community level. Here we present a time series of H2O2 concentrations during a 28-day mesocosm experiment where a pCO2 gradient (400-1450 µatm) was applied to subtropical North Atlantic waters. Pronounced changes in H2O2 concentration were observed over the duration of the experiment. Initially H2O2 concentrations in all mesocosms were strongly correlated with surface H2O2 concentrations in ambient seawaters outside the mesocosms which ranged from 20-92 nM over the experiment duration (Spearman Rank Coefficients 0.79-0.93, p values <0.001-0.015). After approximately 9 days of incubation however, H2O2 concentrations had increased across all mesocosms, later reaching >300 nM in some mesocosms (2-6 fold higher than ambient seawaters). The correlation with ambient H2O2 was then no longer significant (p >0.05) in all treatments. Furthermore, changes in H2O2 could not be correlated with inter-day changes in integrated irradiance. Yet H2O2 concentrations in most mesocosms were inversely correlated with bacterial abundance (negative Spearman Rank Coefficients ranging 0.59-0.94, p values <0.001-0.03). Our results therefore suggest that ambient H2O2 concentration can be influenced by microbial community structure with shifts towards high bacterial abundance correlated with low extracellular H2O2 concentrations. We also infer that the nature of mesocosm experiment design, i.e. the enclosure of water within open containers at the ocean surface, can strongly influence extracellular H2O2 concentrations. This has potential chemical and biological implications during incubation experiments due to the role of H2O2 as both a stressor to microbial functioning and a reactive component involved in the cycling of numerous chemical species including, for example, trace metals and haloalkanes.